2009
DOI: 10.1074/jbc.m109.056309
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and Endocytosis for Cell-penetrating Peptide Internalization

Abstract: Cell-penetrating peptides (CPPs) share the property of cellular internalization. The question of how these peptides reach the cytoplasm of cells is still widely debated. Herein, we have used a mass spectrometry-based method that enables quantification of internalized and membrane-bound peptides. Internalization of the most used CPP was studied at 37°C (endocytosis and translocation) and 4°C (translocation) in wild type and proteoglycandeficient Chinese hamster ovary cells. Both translocation and endocytosis ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
303
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 291 publications
(328 citation statements)
references
References 44 publications
24
303
0
1
Order By: Relevance
“…This low temperature condition only led to a minor reduction in cell penetration ( Fig. 2A) (15,17,18). In addition, cytosolic penetration was achieved in a relatively high percentage of cells within 1 or 3 min of incubation, making a process involving endocytosis and endosomal escape upon slow endocytic maturation unlikely (typical time frame varies from 5 to 30 min) (Fig.…”
Section: Identification Of Efficient Cpps and Robustmentioning
confidence: 99%
See 2 more Smart Citations
“…This low temperature condition only led to a minor reduction in cell penetration ( Fig. 2A) (15,17,18). In addition, cytosolic penetration was achieved in a relatively high percentage of cells within 1 or 3 min of incubation, making a process involving endocytosis and endosomal escape upon slow endocytic maturation unlikely (typical time frame varies from 5 to 30 min) (Fig.…”
Section: Identification Of Efficient Cpps and Robustmentioning
confidence: 99%
“…1B). This staining is common for arginine-rich peptides, and because cytosolic entry presumably precedes nucleolar staining, it indicates that CPPs reach the intracellular cytosolic/nuclear milieu (15)(16)(17)(18). Importantly, this specific staining was observable at ϫ20 magnification for D-CPPs but not for L-CPPs (Fig.…”
Section: Identification Of Efficient Cpps and Robustmentioning
confidence: 99%
See 1 more Smart Citation
“…These cell-penetrating peptides are more or less amphipathic peptides generally rich in lysyl and arginyl residues. It is now well accepted that these peptides can enter cells through direct translocation and endocytosis pathways and thus that they can end up into the cytosol of the cell (5,6). In addition, cell-penetrating peptides are widely used as conjugates to vehiculate inside bioactive molecules of the cell such as peptides, proteins, or nucleic acids (7,8).…”
mentioning
confidence: 99%
“…It has also been demonstrated that CPPs have the capacity to shuttle bioactive cargoes inside eukaryotic cells. The final localization in the cell of the CPP/cargo conjugates or complexes is undoubtedly associated with the mechanism of entry; however, the mechanism is still an ongoing matter of debate [7][8][9][10][11][12][13][14][15][16][17]. The capacity for CPPs to deliver a bioactive molecule inside of cells has opened avenues for intracellular pharmacology, and recently, significant advances have been accomplished for siRNA delivery and also for specific Laurence Dutot and Pascaline Lécorché contributed equally Electronic supplementary material The online version of this article (doi:10.1007/s12154-009-0031-9) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%